Rethinking Japanese Feminisms 2017
DOI: 10.21313/hawaii/9780824866693.003.0016
|View full text |Cite
|
Sign up to set email alerts
|

On Rethinking Japanese Feminisms

Abstract: The conclusion begins by considering the historical and political context of the 2013 conference at Emory University that inspired the edited volume. It questions the meaning of “Womenomics” proposed by Prime Minister Abe Shinzō after his return to power in 2012, and asks what it means to rethink feminism as well as the category of “Japanese” at this historical juncture. Weaving together ideas from the keynote addresses of Ueno Chizuko, Barbara Molony, and Vera Mackie, the chapter considers the issues of canon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…[5][6][7] The first step was to improvement of duration and decision-making process for peer-reviewing papers. 8,9 From an author side, it is natural that the paper must be published as soon as possible after it is written. A questionnaire survey for publications by ECSJ members and authors of papers clearly showed it.…”
Section: Accelerated Decision-makingmentioning
confidence: 99%
See 2 more Smart Citations
“…[5][6][7] The first step was to improvement of duration and decision-making process for peer-reviewing papers. 8,9 From an author side, it is natural that the paper must be published as soon as possible after it is written. A questionnaire survey for publications by ECSJ members and authors of papers clearly showed it.…”
Section: Accelerated Decision-makingmentioning
confidence: 99%
“…The time from submission to early publication is now about five weeks, which is a fairly short review period for a journal that mainly publishes full papers. 8,9 In the post-acceptance process, early publication is done in the manuscript version, and the author's proofreading is also done by using the published Uncorrected Proof. 9 This also contributes to the automation of routine tasks.…”
Section: Accelerated Decision-makingmentioning
confidence: 99%
See 1 more Smart Citation